Hubungan Amplitudo Gelombang Fibrilasi dengan Irama kembali ke Sinus pada Pasien Non Valvular Recent Onset Atrial Fibrillation - Chandra Wijaya; Irwan Irwan (Jurnal Ilmu Kedokteran, 2017)
Atrial fibrillation (AF) is a strong risk factor for death with an increase from 1.5 to 1.9 times in the analysis ofFramingham. A Fis also associated with an increase of 5 times the incidence of stroke. Many studies have attemptedto search for any parameters that can predict whether the AFin patients with recent-onset FA can still return to sinusrhythm mornot, but the results still un satisfactory. This is a descriptive analytic study. The subjects were all patientswith recent onset atrial fibrillation (<72 hours). Analysis test conducted by test unpaired T-test for numerical variablesand chi-square test for categorical variables. From 68 subjects there were 36 patients (52.9%) with return to sinus.After analysis showed that Coarse AF (95% CI 0.11 to 0.82, P=0.017) have significant relationship return to sinus inpatients with recent onset atrial fibrillation.